Preparation and properties of high melt strength PBS and its environmentally friendly foaming materials. Issue 1 (January 2022) - Zhou, Xiao-Ming; Liu, Yi-Fan
In order to improve the melt strength of Poly(butylene succinate) (PBS) resin, the silane graft-crosslinked PBS copolyester materials were prepared by melt blending method with vinyltriethyl silane as graft material and benzyl peroxide (BPO) as initiator. At the same time, the environmentally friendly compound foaming agent (citric acid and sodium bicarbonate) was used as foaming agent. The results showed that the tensile properties and melt strength of PBS resin were greatly improved after silane grafting and cross-linking, and the graft and cross-linking reaction between PBS resin and silane occurred, forming a three-dimensional space network structure, and the viscosity and elasticity of polymer melt was changed, which increased the entropy elasticity of the material and strengthened the polymer melt strength. The additional amount of compound foaming agent and the cross-linking degree of material had important influence on the diameter and distribution of PBS foaming material.